Challenges in Diagnosis and Treatment of Neonatal Ventriculitis: A Case Report and Systematic Review of Difficult-to-Treat Central Nervous System Infection Resistant to Conventional Therapy - Ongun, Hakan; Kihtir, Zeynep; Zarif, Nurten Ozkan; Ozyurt, Ozlem Koyuncu; Kara, Tugce Tural; Celik, Kiymet; Arayici, Sema (Journal of Pediatric Infectious Diseases, 2024)
Objective Ventriculitis is an example of the increasing global trend in difficult-to-treat infections in neonates caused by pathogens resistant to conventional therapies. This article describes the first use of intravenous and intraventricular tigecycline to treat ventriculitis caused by vancomycin-resistant enterococci in a preterm neonate and systematically review the literature on challenges posed by the definitions, diagnosis, and treatment of neonatal ventriculitisMethods The authors searched PubMed and Internet search engines for “ventriculitis” in the period from 2003 to 2023 restricting the research to “Newborn,” “Human,” “English language,” and “full-text availability.”Results Thirty-seven publications (20 case reports, 6 case series, and 11 research articles) were extracted upon research. Preterm birth, posthemorrhagic ventricular dilatation requiring placement of ventricular access devices, and sepsis preceded neonatal ventriculitis. Infections caused by rare microorganisms, in particular gram-negative bacteria resistant to conventional therapies, predominated in the publications describing the need for a combination of intravenous (IV) and intraventricular (IVT) therapies. Survivors of neonatal ventriculitis developed neurodevelopmental impairments such as hydrocephalus, seizures, motor function, hearing, and vision impairment.Conclusion Clinical suspicion of ventriculitis indicated by subtle signs is key for prompt diagnosis. Effective IV and IVT antibiotics are essential to prevent serious sequelae and mortality. The drug delivery method should be changed if there is no clinical response. This study emphasizes the urgent need for pediatric trials of antibiotics against organisms resistant to other drugs.
Keywords: central nervous system infection; preterm neonate; tigecycline; intraventricular treatment